2016
DOI: 10.1016/j.jsv.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired canopies for the reduction of roughness noise

Abstract: This work takes inspiration from the structure of the down covering the flight feathers of larger species of owls, which contributes to their ability to fly almost silently at frequencies above 1.6 kHz. Microscope photographs of the down show that it consists of hairs that form a structure similar to that of a forest. The hairs initially rise almost perpendicular to the feather surface but then bend over in the flow direction to form a canopy with an open area ratio of about 70%. Experiments have been performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…The analytic work of Howe (1998) presents a simplified picture of a line vortex interacting with the trailing edge of a semi-infinite flat plate and predicts the effects of a rigid trailing-edge condition on the acoustic scattering. With this boundary condition being key to the total level of far-field noise generated by turbulence-edge interaction, it is clear why the next steps into the investigation of reducing trailing-edge noise were to consider adapted trailing edge designs, for example a serrated edge (Lyu et al 2016;Oerlemans 2016), a rough surface canopy (Clark et al 2016), or a porous and/or flexible edge (Jaworski & Peake 2013;Schlanderer & Sandberg 2016;Geyer & Sarradj 2014). These adapted designs are inspired by the silent flight of owls, first discussed by (Graham 1934), and now with increasing pressure on the aviation industry to reduce aircraft noise (European Commission 2011) are of great interest worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The analytic work of Howe (1998) presents a simplified picture of a line vortex interacting with the trailing edge of a semi-infinite flat plate and predicts the effects of a rigid trailing-edge condition on the acoustic scattering. With this boundary condition being key to the total level of far-field noise generated by turbulence-edge interaction, it is clear why the next steps into the investigation of reducing trailing-edge noise were to consider adapted trailing edge designs, for example a serrated edge (Lyu et al 2016;Oerlemans 2016), a rough surface canopy (Clark et al 2016), or a porous and/or flexible edge (Jaworski & Peake 2013;Schlanderer & Sandberg 2016;Geyer & Sarradj 2014). These adapted designs are inspired by the silent flight of owls, first discussed by (Graham 1934), and now with increasing pressure on the aviation industry to reduce aircraft noise (European Commission 2011) are of great interest worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Certain features of the wings of owls are known to be particularly effective in reducing scattered noise (Graham 1934): the fringed or serrated trailing edge (Howe 1991); the downy coat on the upper surface of the wing (Clark 2014); and the flexible and porous qualities of the feathers at the trailing edge (Jaworski & Peake 2013). It is this latter feature that we discuss in detail here, by modelling the flexible and porous qualities of the trailing edge of an owl's wing.…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbines are therefore braked when the wind is at all high to minimize noise, impairing their efficiency. Microscopic observation found that owl wing feathers are different from nearly all other birds: They sprout hairs rising almost perpendicularly from the surface that are able to bend in unison with air flow during flight to form a canopy with a large open area [7]. The principle is similar to a forest whose trees can bow together in the direction of the wind to reduce the exposed area and absorb the shock more effectively, although the evolutionary motive was different.…”
Section: Inspiration From Birdsmentioning
confidence: 99%
“…While the canopy can produce its own sound, particularly at high frequencies, the reduction in fluctuations also reduces the noise from the underlying rough surface at lower frequencies, which are audible to many owls' prey. This principle has been applied in a newly designed material that mimics the wing structure of owls [7]. The potential applications include computer fans and airplane engines, as well as wind turbines.…”
Section: Inspiration From Birdsmentioning
confidence: 99%